Nonneutralizing antibodies in Nordic persons with moderate hemophilia A and B (the MoHem study) - Ragnhild J. Måseide, MD, PhD; Erik Berntorp, MD, PhD; Jan Astermark, MD, PhD; Anna Olsson, MD, PhD; Maria Bruzelius, MD, PhD; Tony Frisk, MD, PhD; Vuokko Nummi, MD, PhD; Riitta Lassila, MD, PhD; Karin Strandberg, MD, PhD; Geir E. Tjønnfjord, MD, PhD; Pål A. Holme, MD, PhD (Research and Practice in Thrombosis and Haemostasis)
Background: The impact of nonneutralizing antibodies (NNAs) in moderate hemophilia is elusive. Objectives: To explore the presence of NNAs in Nordic persons with moderate hemophilia A (MHA) and B (MHB) in relation to treatment modality, clinical outcome, history of inhibitor, and the corresponding factor VIII (FVIII)/factor IX (FIX) gene mutation. Methods: A cross-sectional multicenter study covering persons with MHA and MHB in Sweden, Finland, and Norway. Inhibitors were analyzed with the Bethesda assay, and NNAs were detected by enzyme-linked immunosorbent assay. Results: Plasma samples from 137 MoHem study participants (median age 29 years; Q1-Q3, 15-54) were analyzed. NNAs were present in 11 of 82 (13%) of people with MHA and 7 of 55 (13%) of those with MHB irrespective of prophylactic or on-demand treatment, most frequently after 150 exposure days (EDs). Three NNA positive patients had a history of high-titer inhibitor, but current analyses were negative (<0.6 BU/mL). Baseline FVIII/FIX activity was similar among NNA positive and negative patients. Current bleeding rates were low, but patients with NNAs captured a higher Hemophilia Joint Health Score (7 [median]; Q1-Q3, 3-20 vs. 4; 1-9) (P = .02) and had more frequently undergone arthroplasty or arthrodesis (5 [33%] vs. 15 [13%]) (P = .03). Conclusion: NNAs were detected in 13% of Nordic persons with MHA and MHB, most frequently after 150 EDs. Patients with NNAs had more severe hemophilic arthropathy than patients without NNAs. The relationship between NNAs and clinical outcome in hemophilia should be further explored in a large cohort including pharmacokinetics and longitudinal observations with repeated blood sampling.